The power of legitimate naming. Part 2 - Making sense of the elite police voice - Loader, Ian (The British journal of criminology, 2001)
In Part I of this paper (Loader and Mulcahy 2001) we set out to trace the coming to prominence since 1945 of an elite police voice with a significant symbolic power to represent and name social problems. In so doing, we charted the transition of chief officers from powerful but essentially local figures (1945-1972), through the rise of maverick, culturally salient police heroes' (1973-1986), to the establishment (from 1987 onwards) of a more corporate and generally liberal police outlook. Here in Part II we develop a sociological interpretation of these documented shifts, by seeking to grasp: (i) contemporary transformations in the professional ideology of police elites; (ii) the relation of those elites to the architecture and programmes of government, and (iii) the changing social and cultural conditions within which the police voice with all its authoritative social magic' has during the post-war period been called forth, transmitted and received